SIKAP DAN KEPUASAN KONSUMEN TERHADAP PRODUK MINUMAN TRADISIONAL BANDREK DI KOTA BANDAR LAMPUNG - Marsaben, Winny Maharani; Indriani, Yaktiworo; Saleh, Yuliana (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This research was conducted to identify the most satisfying atributes  at Kedai Bandrek Uus and Kedai Bandrek Istimewa Enggal, Bandar Lampung City. There were many attributes of consumers consider important, among of attributes, the shop owner must be able to categories which attributes were considered important of which attributes of the shop were deemed satisfactory. Therefore, this research was conducted to find out what consumers' attitudes are and which attributes need to be maintained to improve the performance of Bandrek shops. This research used survey methodology and involved 60 samples from  both Bandrek shops. This research used  the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) analysis methods. The result of the  research shows that consumer attitudes towards the traditional Bandrek drink are in good category with the highest attributes considered as  important are  parking lots, service, and the taste of bandrek. Consumer satisfaction of  Bandrek drinks in Bandar Lampung City is categorized as very satisfying with score reach to  86.6 percent in related  attributes of parking lots and the taste of the drink, that both are in first quadrant (Top Priority), and there are   2 attributes in second quadrant that need to maintain achievement, namely price and service. Another 2 attributes in third quadrant with  low priority), namely location and aroma, while in fourth quadrant there are variation attributes. Keywords: bandrek, CSI, IPA, satisfactory